DAYA SAING DAN SENSITIVITAS USAHATANI JAGUNG DI KABUPATEN PACITAN - Lorenta In Haryanto; Masyhuri Masyhuri; Irham Irham (Jurnal Kawistara, 2018)
Strengthening competitiveness is an important factor in facing the growth of international trade in commodity markets, especially for maize as feed commodities.This research aims to: (1) analyze the level of profit and competitiveness of maize farming, (2) investigate farming components affecting competitiveness, and (3) analyze sensitivity level of profit and competitiveness towards the changes. Data were processed using PAM (Policy Analysis Matrix) and sensitivity analysis. The research was conducted on March- May 2018 in Pacitan with 102 maize farmers as sample respondents, collected proportionally. Sensitivity analysis observed four changes, i.e; increase of purchase price, the structure of labor, optimization of maize productivity, and weakening of rupiah exchange rate. Research findings indicated that (1) maize farming in Pacitan does not generate either financial or economic profits, as well as competitiveness, as shown by PCR and DRCR accounting for 1,033 and 1,024 respectively; (2) the component influencing competitive advantages is purchase price and component influencing comparative advantages is rupiah exchange rate; components simultaneously influencing both advantages are structure of labor and maize productivity; (3) the sensitivity analysis proves that the changes of profit are elastic towards the changes of four components indicated by elasticity indicator with a value of more than one. The changes of competitiveness are elastic only for purchase price, but for other components they are inelastic.